[OA108] Quantitative analysis of ventilation SPECT applied to krypton and technegas. (August 2018) - Nijs, Robin; Sijtsema, Nienke Desiree; Kruis, Matthijs; Perch, Michael; Mortensen, Jann
Abstract : Purpose: Assessment of the state of the lungs by ventilation perfusion (V/Q) Single Photon Emission Computed Tomography combined with Computed Tomography (SPECT/CT) has proved its value as a clinical tool. Physicians study both ventilation and perfusion images, but also the ratio image of these two. However, the interpretation of these images is qualitative. For the ventilation images quantitative measures were investigated in the case of Krypton-81 m and Technegas (Tc-99 m labelled graphite particles). Krypton is a gaseous ventilation tracer and distributes similarly to air. However, it is not widely available and relatively expensive. Technegas is cheaper and has wider availability, but is an aerosol, which may result in hot spots in obstructed airways. Methods: Dual-isotope ventilation SPECT/CT with both Technegas(140 keV) and Krypton(190 keV) simultaneously was obtained for 11 patients with medium and low energy general purpose collimators including a follow-up. This resulted in 38 ventilation studies in total. Reconstruction was performed with and without attenuation and scatter correction. The penetration index and the heterogeneity index (with and without band filtering for relevant clinical sizes) were calculated for the right and left lung. Scatterplots of the intensities of the Krypton and Technegas images were made and statistical outliers were detected. Results: Significant lower penetration indexes for Technegas were found for the medium energy collimators, but were not seen for the low energy collimators. The higher heterogeneity indexes for Technegas were significant in all cases except for the uncorrected medium energy collimators data. Band filtering of the heterogeneity index improved the statistical significance of the differences. The scatterplots showed that all patients suffered from Technegas-outliers in one or both lungs, indicating the presence of hot spots. The visually identified hot spots could be mapped to the outliers seen in the scatterplots. Conclusions: The applied quantitative analysis revealed that there are significant differences between Krypton and Technegas as a ventilation tracer for patients with severe COPD. The penetration index may have limited clinical relevance, since it does not capture complicated activity distributions. However, the heterogeneity index with band filtering is potentially a useful quantitative clinical measure.